(untitled) (Berceo, 2024)
Satirical press and visual language offer us an enormously valuable source of information for studying political cultures and their most prominent representatives. Through the caricatures shown in the newspapers, a certain public could access humorous, critical and distortingreadings of political life, finding symbology and ideological attributionslinked to the profile of the publications. What we bring here is the consideration of a new and unknown support of these cartoons: the labels that decorated the matchboxes. They also reproduced the same representations and scenes that simultaneously occupied the pages of the newspapers.Using a series of these labels, we undertake an unprecedented biographical reconstruction of PráxedesMateo- Sagasta, from a new look and the cartoons.